Minimal observed impact of HLA genotype on hospitalization and severity of SARS‐CoV‐2 infection. (24th February 2022) - Nguyen, Austin; Yusufali, Tasneem; Hollenbach, Jill A.; Nellore, Abhinav; Thompson, Reid F.
Abstract : HLA is a critical component of the viral antigen presentation pathway. We investigated the relationship between the severity of SARS‐CoV‐2 disease and HLA type in 3235 individuals with confirmed SARS‐CoV‐2 infection. We found only the DPB1 locus to be associated with the binary outcome of whether an individual developed any COVID‐19 symptoms. The number of peptides predicted to bind to an HLA allele had no significant relationship with disease severity both when stratifying individuals by ancestry or age and in a pooled analysis. Overall, at the population level, we found HLA type is significantly less predictive of COVID‐19 disease severity than certain demographic factors and clinical comorbidities.